ACESSIBILIDADE E MULTIMIDIALIDADE NO WEBJORNALISMO DA AMÉRICA DO SUL - Segatto, Karine Arminda de Fátima (2015)
This research discusses the form of news presentation in web journalism in face of international standards for web accessibility for people with disabilities in 10 countries in South America that are signatories to the International Rights Convention for People with Disabilities: Argentina, Brazil, Bolivia, Chile, Colombia, Ecuador, Paraguay, Peru, Uruguay and Venezuela. The potential of web multimidiality was confronted with accessibility, in means to find the limitations and potential of web journalism on this aspect. Required standard methodology was used, created from the WCAG accessibility guidelines, multimidiality characteristics in web journalism, and found pattern, which is the result of analysis in accessibility hypermedia elements present in 152 news samples. The sample was composed by websites: Todo Noticias (http://tn.com.ar/); Folha de S. Paulo (http://www.folha.uol.com.br/); La Razón (http://la-razon.com/); BioBioChile (http://www.biobiochile.cl/); El Espectador (www.elespectador.com); El Universo (http://www.eluniverso.com/); Paraguay (http://www.paraguay.com/); El Comercio (http://elcomercio.pe); Montevideo (http://montevideo.com.uy/); and Últimas Noticias (www.ultimasnoticias.com.ve). The objective was to demonstrate the extent to which online news sites are contemplating the universality of rights to information.